Effect of shared decision making on mode of delivery and decisional conflict and regret in pregnant women with previous cesarean section: a randomized clinical trial - Fatemeh Hadizadeh-Talasaz; Faezeh Ghoreyshi; Fatemeh Mohammadzadeh; Roghaieh Rahmani (BMC, 2021)
Abstract Background The promotion of vaginal birth after cesarean section (VBAC) is the best method for the reduction of repeated cesarean sections. Nonetheless, the decisional conflict which often results from inadequate patient involvement in decision making, may lead to delayed decision making and regret about the choices that were made. The present study aimed to determine the effect of shared decision making on the mode of delivery and decisional conflict and regret in pregnant women with previous cesarean section. Methods This randomized clinical trial was conducted on 78 pregnant women with a previous cesarean section referring to community health centers in Torbat-e Jam, Iran, in 2019. They were randomly assigned to two groups of intervention and control. During weeks 24-30 of pregnancy, the Decisional Conflict Scale (DCS) was completed by pregnant mothers. Apart from the routine care, the experimental group received a counseling session which was held based on the three-talk model of shared decision making. This session was moderated by a midwife; moreover, a complementary counseling session was administered by a gynecologist. During weeks 35-37 of pregnancy, DCS was completed, and the Decision Regret Scale (DRS) was filled out for both groups at the 8th weeks postpartum and they were asked about the mode of delivery. Data were analyzed in SPSS software (version 19) using the Mann-Whitney, Chi-squared and Fisher's exact tests. p-value less than 0.05 was considered statistically significant. Results After the intervention, the decisional conflict score was significantly lower in the shared decision making (SDM) group, compared to that in the control group (14.90 ± 9.65 vs. 25.41 ± 13.38; P < 0.001). Moreover, in the SDM group, the rate of vaginal birth was significantly higher than that in the control group (P < 0.001). Two month after the delivery, the mean score of decision regret was lower in the SDM group, in comparison to that in the control group (15.67 ± 23.37 vs. 27. 30± 26.75; P = 0.007). Conclusions Based on the results of the study, shared counseling can be effective in the reduction of decisional conflict and regret, as well as rate enhancement of VBAC. Therefore, it can be concluded that this counseling method can be used in prenatal care to reduce the rate of repeated cesarean section. Trial registration IRCT20190506043499N1; Name of the registry: Iranian Registry of Clinical Trials; Registered 10. August 2019. URL of registry: https://en.irct.ir/trial/39538. Date of enrolment of the first participant to the trial: August 2019.